Quadruple Helix Collaboration Mapping for Fashion Economic Development in Bandung - Hudani, Hafiz; Dhewanto, Wawan (Journal of Business and Management, 2015)
Abstract. Quadruple Helix is a system of collaboration between university, industry, government and citizen. Quadruple Helix consists of government as policy maker, university as researcher, industry as economic driver manufacturer plus community as connector between the three actors. Bandung is known as the city of fashion, as we can see from the large quanity of both supply and demand for fashion industry. This is an indication that Bandung has huge potential for creative industry development especially fashion. The aim of this study is to mapping and maximize the potential of QH actors in Bandung. The output of this research is Quadruple Helix program master plan. This research was conducted with qualitative methodology which are field observation, direct interview, secondary data and descriptive analysis for 1 year.Â Keywords: Quadruple Helix, University-Industry-Government-Community interaction, Economic Development, Creative Industry, Fashion, Small Medium Enterprise